If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(9a) = x + 6 Remove parenthesis around (9a) F * 9a = x + 6 Reorder the terms for easier multiplication: 9F * a = x + 6 Multiply F * a 9aF = x + 6 Reorder the terms: 9aF = 6 + x Solving 9aF = 6 + x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '9F'. a = 0.6666666667F-1 + 0.1111111111xF-1 Simplifying a = 0.6666666667F-1 + 0.1111111111xF-1
| 6(-5x+7)=8(4x-6) | | f=3x^2+5 | | 99999999999999999999999999= | | 2x+2y-6x+5x^2-7y= | | 4x-24=-7x-28 | | 2m+m-(m-2)= | | 2(X-1)/5 | | 2tanx+9=0 | | 0.32+0.23(x-1)=19 | | 10=4a+3 | | 0.33+0.23(x-1)=19 | | 5x+8y=-7 | | (4x+3)(7x-5)= | | 4.4x-10.88=5.4 | | 0=0.04t^2+2t-200 | | 7x+2(6x+9)=170 | | 2x-5(x-3)=0 | | (36/5(5/14)/(-5/4) | | x/-4-3=7 | | 2/5×5 | | 3-8k=-125 | | f(-4)f(x)=x^2-3x+9 | | Y=-6/5x-12/5 | | 0=0.04(t^2-50t+5000) | | 0=12x^2-84x+80 | | A/a-b=-2/a-1 | | 5(3.14)= | | v=x(16-2x)(5-2x) | | 5(x-3)=3(x+7)+x | | a(3)=16/3(3/2)^3-1 | | Y-(6-2y)=8(y-2) | | 0=12x^2-80x+84 |